Effect of Cyclosporin A and Angiotensin II on cytosolic calcium levels in primary human gingival fibroblasts - Ajitkumar Supraja; Murugan Girija Dinesh; Subbarayan Rajasekaran; Thodur Madapusi Balaji; Suresh Ranga Rao (Wolters Kluwer Medknow Publications, 2016)
Background: To evaluate the effect of Cyclosporin A (CsA) and angiotensin II (Ang II) on cytosolic calcium levels in cultured human gingival fibroblasts (HGFs). Materials and Methods: Healthy gingival samples from six volunteers were obtained, and primary HGFs were cultured. Cell viability and proliferation assay were performed to identify the ideal concentrations of CsA and Ang II. Cytosolic calcium levels in cultured gingival fibroblasts treated with CsA and Ang II were studied using colorimetric assay, confocal and fluorescence imaging. Statistical analyses were done using SPSS software and GraphPad Prism. Results: Higher levels of cytosolic levels were evident in cells treated with CsA and Ang II when compared to control group and was statistically significant (P < 0.05) in both colorimetric assay and confocal imaging. Fluorescent images of the cultured HGFs revealed the same. Conclusion: Thus calcium being a key player in major cellular functions, plays a major role in the pathogenesis of drug-induced gingival overgrowth.